Long-term testosterone depletion attenuates inflammatory bone resorption in the ligature-induced periodontal disease model - Goncalves, Vincius de Paiva [UNESP]; Ortega, Adriana Alicia C. [UNESP]; Steffens, Joao Paulo; Palomari Spolidorio, Denise Madalena; Rossa Junior, Carlos [UNESP]; Spolidorio, Luis C. [UNESP] (Amer Acad Periodontology, 2018)
Background: Testosterone is known to affect bone in physiological and pathological conditions. The purpose of this study is to evaluate the role of testosterone in experimental periodontal disease in rats. Methods: In this study we used a ligature model of periodontal disease in rats submitted to orchiectomy (OCX, testosterone depletion) with and without testosterone replacement therapy (TR). Control animals were sham-operated and retained physiological testosterone levels. Sixty-two days after orchiectomy and sham operations, ligatures were placed around the lower first molars for 2 weeks to induce experimental periodontal disease. Negative control animals received no ligatures. The outcomes assessed in the periodontal tissues were: inflammatory cytokine expression by enzyme-linked immunosorbent assay (ELISA), stereometric analysis of the inflammatory process and quantitation of inflammatory bone resorption by microcomputed tomography (mu-CT). Results: The OCX+TR group showed the greatest increase in fibroblastic cells and blood vessels with reduced inflammatory cell numbers in the gingival tissue with induction of periodontal disease. There were no significant differences between OCX and Sham-operated groups in all the stereometric parameters assessed. Ligature placement induced inflammatory bone resorption, which was significantly attenuated in OCX animals. Experimental periodontitis induced a significant increase in interleukin (IL)-1 beta, but the lowest levels were observed in the periodontitis/OCX group. IL-6 levels were not affected by OCX, but were significantly reduced in OCX+TR animals. Conclusion: The findings of the present study suggest that testosterone depletion attenuates inflammatory bone resorption in ligature-induced periodontitis, which may be partly mediated via decreased production of IL-1 beta.
Keywords: inflammation; periodontitis; testosterone